Physiological Roles of DNA Double-Strand Breaks - Farhaan A. Khan; Syed O. Ali (Journal of Nucleic Acids)
Genomic integrity is constantly threatened by sources of DNA damage, internal and external alike. Among the most cytotoxic lesions is the DNA double-strand break (DSB) which arises from the cleavage of both strands of the double helix. Cells boast a considerable set of defences to both prevent and repair these breaks and drugs which derail these processes represent an important category of anticancer therapeutics. And yet, bizarrely, cells deploy this very machinery for the intentional and calculated disruption of genomic integrity, harnessing potentially destructive DSBs in delicate genetic transactions. Under tight spatiotemporal regulation, DSBs serve as a tool for genetic modification, widely used across cellular biology to generate diverse functionalities, ranging from the fundamental upkeep of DNA replication, transcription, and the chromatin landscape to the diversification of immunity and the germline. Growing evidence points to a role of aberrant DSB physiology in human disease and an understanding of these processes may both inform the design of new therapeutic strategies and reduce off-target effects of existing drugs. Here, we review the wide-ranging roles of physiological DSBs and the emerging network of their multilateral regulation to consider how the cell is able to harness DNA breaks as a critical biochemical tool.